Covalent organic polymer material based on polyquinone imidazole, preparation method of covalent organic polymer material and application of covalent organic polymer material in lithium ion battery negative electrode material

By adopting the covalent organic polymer materials HATTABQ and HATTAPT based on polyquinone imidazole, the problem of insufficient cyclic stability and capacity retention rate of lithium-ion battery anode materials under high current density is solved, and a lithium-ion battery anode materials with high capacity and good stability is achieved.

CN119842072AActive Publication Date: 2025-04-18LIAONING UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510026007.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-18
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

It is difficult for existing lithium-ion battery anode materials to achieve long cycle stability and capacity retention under high current density, and the structural stability and conductivity are insufficient.

Method used

Using the covalent organic polymer materials HATTABQ and HATTAPT based on polyquinone imidazole, materials with high lithium storage capacity are prepared through specific synthesis methods and process steps and applied to the negative electrode materials of lithium-ion batteries.

Benefits of technology

The high capacity and good stability of the negative electrode material of lithium-ion battery were achieved. The HATTABQ electrode can circulate stably for 20,000 turns at 10A/g current density, with a capacity retention rate of 78.4%; the HATTAPT electrode can circulate stably for 2000 turns at 5A/g current density, with a capacity retention rate of 64.3%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842072A_ABST
    Figure CN119842072A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and discloses a polyquinoneimidazole-based covalent organic polymer material, a preparation method thereof and an application of the polyquinoneimidazole-based covalent organic polymer material in a lithium ion battery negative electrode material. The preparation method comprises the following steps: carrying out a hydrothermal synthesis reaction on hexaaza-naphthalene carboxylic acid (HAT-6COOH) and tetraamino p-benzoquinone (TABQ) or 2, 3, 7, 8-tetraamino-1, 4, 6, 9-tetraquinone phenazine (TAPT) to prepare two kinds of polyquinoneimidazole organic polymer materials, and respectively recording the two kinds of polyquinoneimidazole organic polymer materials as HATTABQ and HATTAPT. The lithium ion battery based on the material disclosed by the invention shows relatively high specific capacity and relatively good cycle stability. Under the current density of 10 A / g, the HATTABQ electrode can reach the specific discharge capacity of 279.2 mAh / g in the first circle, the HATTABQ electrode can stably circulate for 20000 circles, and the capacity retention ratio is 78.4%. Under the current density of 5A / g, the HATTAPT electrode can reach the specific discharge capacity of 473.8 mAh / g in the first circle, the HATTAPT electrode can be stably circulated for 2000 circles, and the capacity retention ratio is 64.3%. The preparation method is simple in process and beneficial to large-scale industrial production, and has potential application value in lithium ion battery negative electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of negative electrode materials for lithium ion batteries, and specifically relates to a class of covalent organic polymer materials (HATTABQ or HATTAPT) based on polyquinone imidazole and a preparation method thereof and application in negative electrode materials for lithium ion batteries. Background Art

[0002] With the strong support of the country for the electric vehicle industry in recent years, as well as the rapid development of smart phones and energy storage grid systems, people's demand for clean and efficient energy storage technology is also increasing. Lithium-ion batteries (LIBs) have almost always been the best choice for energy storage devices due to their small size, long cycle life, high power density, and low self-discharge rate, dominating the market for rechargeable batteries for mobile electronic devices and electric vehicles.

[0003] In the research of lithium-ion batteries, in addition to factors such as positive electrode materials and electrolytes, negative electrode materials also largely determine the overall performance of the battery. In order to promote the industrialization and practical application of high-performance lithium-ion batteries, researchers have invested a lot of energy in the research of negative electrode materials. At present, carbon-based materials, silicon-based materials, tin-based materials, transition metal oxides and sulfides are mainly used as negative electrode materials for lithium-ion batteries. Among them, the commercially available graphite has a theoretical capacity of only 372 mAhg -1 , lithiated graphite also brings safety issues. In contrast, organic polymer electrode materials have attracted increasing attention due to their high theoretical specific capacity, high safety, environmental friendliness, low cost and flexible design, and are considered to be candidates for the next generation of green electrode materials for lithium-ion batteries. However, due to the weak structural stability and low conductivity of organic polymers, achieving long cycle stability and capacity retention at high current density remains an important challenge.

[0004] Covalent organic frameworks (COFs) are a new type of crystalline organic porous polymer with high specific surface area, long-range ordered structure and adjustable functionalization, which is very different from traditional polymers. The uniform pore structure in the network structure of COFs materials and the redox active sites on the surface and near the surface are conducive to improving Li +The transport kinetics of COFs materials are poor, but some redox active sites in COFs materials are not fully utilized due to the deep burial of active sites inside the COFs materials due to the high-density stacked two-dimensional layered structure, which leads to a decrease in reversible specific capacity. In addition, COFs are usually formed by reversible covalent bonds C=N (usually formed by the combination of aldehyde groups and amino groups), which are easy to break under extreme conditions, so the chemical stability is poor, which limits the application of COFs in lithium-ion batteries. In contrast, covalent organic polymer materials (COPs) are another type of porous organic polymers formed by irreversible strong covalent bonds, which have excellent chemical stability and exist in semicrystalline or amorphous forms, which enables them to exist stably in harsh chemical environments. The quinone imidazole repeating units of the two COP materials involved in the present invention are formed by the combination of carboxyl groups and amino groups, which are more stable than the C=N formed by the combination of aldehyde groups and amino groups. At the same time, thanks to this amorphous structure, the active sites of the polyquinone imidazole covalent organic polymers involved in the present invention can be effectively exposed to the electrochemical environment, showing a higher specific capacity. Therefore, rationally designing new and highly stable organic electrode materials for use in LIBs anode materials to solve these problems is crucial to improving the performance of LIBs. Summary of the invention

[0005] The invention relates to a type of polyquinone imidazole covalent organic material with high lithium storage capacity and a preparation method thereof and application in lithium ion batteries, aiming to provide a covalent organic material with high energy storage and cycle stability.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A class of covalent organic polymer materials based on polyquinone imidazoles includes HATTABQ and HATTAPT, wherein the structural formulas of HATTABQ and HATTAPT are shown in (I) and (II), respectively:

[0008]

[0009] Furthermore, the preparation method of the above-mentioned class of covalent organic polymer materials based on polyquinone imidazole, HATTABQ, comprises the following steps: dispersing compound 1 and compound 2 in ultrapure water, adding a catalyst, placing in a reaction kettle, reacting at 180° C. for 3 days, filtering, washing, and drying to obtain a black product HATTABQ;

[0010] The preparation method of HATTAPT comprises the following steps: dispersing compound 1 and compound 3 in ultrapure water, adding a catalyst, placing in a reaction kettle, reacting at 180° C. for 3 days, filtering, washing, and drying to obtain a black product HATTAPT;

[0011] The compound 1 is hexaazine naphthylazolic acid, the compound 2 is tetraaminobenzoquinone, and the compound 3 is 2,3,7,8-tetraamino-1,4,6,9-tetraquinone phenoloxazine.

[0012] Furthermore, in the above-mentioned class of covalent organic polymer materials based on polyquinone imidazole, the structural formulas of compound 1, compound 2 and compound 3 are shown as (III), (IV) and (V), respectively:

[0013]

[0014] Furthermore, in the above-mentioned type of covalent organic polymer material based on polyquinone imidazole, the catalyst is 3M acetic acid solution.

[0015] Furthermore, in the above-mentioned class of covalent organic polymer materials based on polyquinone imidazole, the molar ratios of compound 1 to compound 2 and compound 1 to compound 3 are both 1:1.5.

[0016] Furthermore, for the above-mentioned type of covalent organic polymer material based on polyquinone imidazole, the drying condition is drying at 60° C. for 12 hours.

[0017] The above-mentioned class of covalent organic polymer materials based on polyquinone imidazole is used as negative electrode materials in lithium-ion batteries.

[0018] Further, the above application method is as follows:

[0019] 1) Mixing the covalent organic polymer material based on polyquinone imidazole according to claim 1 with the conductive agent Super P and the binder CMC, adding the solvent H2O to grind into a uniform and particle-free slurry, and evenly scraping the slurry on the current collector with a tetrahedral mold;

[0020] 2) Place the coated current collector in a 60°C vacuum drying oven and dry for 12 hours to remove the residual solvent, and then cut it into a circle with a diameter of 12 mm using a cutting machine to obtain an electrode sheet;

[0021] 3) In an argon-protected glove box, the water and oxygen values ​​in the glove box are kept less than 0.1 ppm, and the electrode sheet, PP diaphragm, electrolyte, metal lithium sheet with a diameter of 16 mm, gasket, spring, and positive electrode shell obtained in step 2) are placed in the negative electrode shell in sequence using a 2032-type button cell standard;

[0022] 4) Use a packaging machine to seal the battery to obtain a 2032-type button lithium-ion battery.

[0023] Furthermore, in the above application method, in step 1), the mass ratio of a class of covalent organic polymer materials based on polyquinone imidazole: Super P: CMC is 6:3:1, and the current collector is copper foil.

[0024] Furthermore, in the above application method, in step 3), the preparation method of the electrolyte is: dissolving LiPF6 in a mixture of EC and DEC so that the concentration of LiPF6 is 1M and the volume ratio of EC and DEC is 1:1.

[0025] The beneficial effects of the present invention are:

[0026] 1. The HATTABQ and HATTAPT synthesized in the present invention exhibit high capacity and good stability as negative electrode materials for lithium-ion batteries. At a current density of 10A / g, the HATTABQ electrode can reach a discharge capacity of 279.2mAh / g in the first cycle, can stably cycle for 20,000 cycles, and the capacity retention rate is 78.4%. At a current density of 5A / g, the HATTAPT electrode can reach a discharge capacity of 473.8mAh / g in the first cycle, can stably cycle for 2,000 cycles, and the capacity retention rate is 64.3%.

[0027] 2. The HATTABQ and HATTAPT synthesized in the present invention can match the current commercial electrolytes and have good compatibility, without the need to develop new electrolytes.

[0028] 3. The HATTABQ and HATTAPT materials of the present invention are easy to synthesize, use water as solvent, and are green, simple and efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 FTIR spectra of HATTABQ (a) and HATTAPT (b).

[0030] Figure 2 are the XRD patterns of HATTABQ (a) and HATTAPT (b).

[0031] Figure 3 The cyclic voltammetry curves of HATTABQ (a) and HATTAPT (b) at different scan rates as negative electrode materials for lithium-ion batteries.

[0032] Figure 4 (a) is the long cycle diagram of HATTABQ as a negative electrode material for lithium-ion batteries at a current density of 10 A / g. Figure 4 (b) is the long cycle diagram of HATTAPT as a negative electrode material for lithium-ion batteries at a current density of 5 A / g.

[0033] Figure 5(a) is the rate diagram of HATTABQ as a negative electrode material for lithium-ion batteries. Figure 5 (b) is the rate diagram of HATTAPT as a negative electrode material for lithium-ion batteries. DETAILED DESCRIPTION

[0034] Experimental Example 1 Preparation of HATTABQ

[0035] Compound 1 hexaazine naphthyridine carboxylic acid (HAT-6COOH) (99.66 mg, 0.2 mmol) and compound 2 tetraaminobenzoquinone (TABQ) (50.44 mg, 0.3 mmol) were ground and mixed evenly, then dispersed in 30 mL ultrapure water, and 1 mL of 3M acetic acid solution was added as a catalyst. After ultrasonic dispersion for 15 min, the mixture was transferred to a 50 mL polytetrafluoroethylene liner, placed in a reactor, and reacted in an oven at 180°C for 3 days; after cooling to room temperature, the product was filtered out with a sand core filter, washed three times with 20 mL ultrapure water and 20 mL DMSO respectively, and then the obtained black product HATTABQ was placed in a vacuum drying oven at 60°C and dried for 12 h. The specific synthesis route is as follows:

[0036]

[0037] Experimental Example 2 Preparation of HATTAPT

[0038] Compound 1 hexaazine naphthyridine carboxylic acid (HAT-6COOH) (99.66 mg, 0.2 mmol) and compound 3 2,3,7,8-tetraamino-1,4,6,9-tetraquinone phenol azine (TAPT) (90.07 mg, 0.3 mmol) were ground and mixed evenly, then dispersed in 30 mL ultrapure water, and 1 mL of 3M acetic acid solution was added as a catalyst. After ultrasonic dispersion for 15 min, the mixture was transferred to a 50 mL polytetrafluoroethylene liner, placed in a reactor, and reacted in an oven at 180 ° C for 3 days; after cooling to room temperature, the product was filtered out with a sand core filter, washed three times with 20 mL ultrapure water and 20 mL DMSO respectively, and then the obtained black product HATTAPT was placed in a vacuum drying oven at 60 ° C and dried for 12 h. The specific synthesis route is as follows:

[0039]

[0040] The obtained materials were characterized by FTIR, and the results were as follows: Figure 1 (a) and Figure 1 (b) is shown. Figure 1 (a) It can be seen that at the infrared characteristic peak 3324cm -1 and 3395cm -1 At 1750 cm -1At 3324 cm, the stretching vibration of C=O(-COOH) of the monomer HAT-6COOH can be found. -1 and 3395cm -1 The infrared characteristic peaks of -NH2 at 1750cm -1 The C=O(-COOH) characteristic peak at 1710 cm -1 The corresponding C=O characteristic peak is 1631cm -1 The stretching vibrations of C=C and C=N are at 1485cm -1 The characteristic peak at 1291 cm is attributed to the C=N stretching vibration of imidazole. -1 The corresponding CN stretching vibration indicates that HATTABQ has been successfully synthesized. Figure 1 In (b), the infrared characteristic peak at 3312 cm -1 and 3373cm -1 At 1750 cm -1 At 1712 cm, it is attributed to the stretching vibration of C=O(-COOH) of the monomer HAT-6COOH. At the same time, the FTIR curve of the product HATTAPT shows that -1 The corresponding C=O characteristic peak is 1600cm -1 The corresponding C=C and C=N characteristic peaks are at 1480cm -1 The characteristic peak at 1282 cm is attributed to the C=N stretching vibration of imidazole. -1 The corresponding CN stretching vibration indicates that HATTAPT has been successfully synthesized. The obtained material was characterized by XRD. Figure 2 (a) and Figure 2 (b) is shown. Figure 2 (a) It can be seen that HATTABQ has a broad peak at 27.34°(002), corresponding to the interplanar spacing of This interplanar spacing is similar to the typical distance of π-π stacking (usually between 3.3 and This indicates that there is a stable π-π stacking structure between HATTABQ layers. At the same time, the intensity of the (002) crystal plane peak is proportional to the degree of graphitization, indicating that HATTABQ has a graphitized structure. Similarly, Figure 2 (b) shows that HATTAPT has a broad peak at 28.1°(002), corresponding to the interplanar spacing of This indicates that there are stable π-π stacking structures and graphitized structures between HATTAPT layers. These stable π-π stacking structures and graphitized structures are conducive to the full exposure of active sites, making the actual specific capacity of the material closer to its theoretical specific capacity.

[0041] Experimental Example 3 Preparation of negative electrode sheet

[0042] HATTABQ or HATTAPT was mixed with Super P and CMC in a mass ratio of 6:3:1, and the solvent H2O was added to grind into a uniform and particle-free slurry. The slurry was evenly scraped on the current collector copper foil with a tetrahedral mold. The coated copper foil was placed in a vacuum drying oven at 60°C and dried for 12 hours to remove the residual solvent. The copper foil was cut into round copper sheets with a diameter of 12 mm using a cutting machine to obtain the negative electrode sheet.

[0043] Experimental Example 4: Assembling a battery

[0044] The battery was assembled in an argon-protected glove box using the 2032-type button cell standard, specifically to keep the water and oxygen values ​​in the glove box less than 0.1 ppm. The negative electrode sheet prepared in Example 3, a PP diaphragm, 40 μL of electrolyte (1 M LiPF6 dissolved in a mixture of EC and DEC in a volume ratio of 1:1), a round lithium sheet with a diameter of 16 mm, a gasket, a shrapnel, and a positive electrode shell were placed in the negative electrode shell in sequence, and then packaged with a packaging machine to obtain a lithium-ion 2032-type button cell. The cyclic voltammetry curve test and electrochemical impedance test were then performed using a Bio-Logic electrochemical workstation, and the constant current charge and discharge test was performed using a LANHE battery testing system.

[0045] After the assembled lithium-ion battery was left to stand at room temperature for 2 hours, cyclic voltammetry test, rate test and long cycle test were performed in the voltage window of 0.01-3V. Figure 3 (a) and 3(b) are the cyclic voltammetry test curves of HATTABQ and HATTAPT for lithium-ion battery negative electrode materials at a scan rate of 0.2mV / s-1mV / s. As the scan rate increases, the current density also increases. Figure 3 (a) It can be seen that for HATTABQ, there is only one pair of redox peaks. When the scan rate is 0.2 mV / s, the oxidation peak is located at 0.8 V (vs. Li / Li + ), the reduction peak is located at 0.4V (vs. Li / Li + );Depend on Figure 3 (b) It can be seen that for HATTAPT, there are two pairs of redox peaks. When the scan rate is 0.2 mV / s, the oxidation peak is located at 0.9 / 1.6 V (vs. Li / Li + ), the reduction peak is located at 0.7 / 1.5V (vs.Li / Li+ ).

[0046] like Figure 4 As shown in (a) and 4(b), the HATTABQ electrode was subjected to a cycle stability test at a current density of 10A / g, and the HATTAPT electrode was subjected to a cycle stability test at a current density of 5A / g. At a current density of 10A / g, the HATTABQ electrode can reach a discharge capacity of 279.2mAh / g in the first cycle, can stably cycle for 20,000 cycles, and the capacity retention rate is 78.4%. The first cycle coulombic efficiency is low, only 50.04%, which may be due to the formation of irreversible SEI film or other side reactions. At a current density of 5A / g, the HATTAPT electrode can reach a discharge capacity of 473.8mAh / g in the first cycle, can stably cycle for 2,000 cycles, and the capacity retention rate is 64.3%. The first cycle coulombic efficiency is also low, only 52.72%.

[0047] like Figure 5 As shown in (a) and 5(b), the HATTABQ and HATTAPT electrodes were tested at different current densities. At a current density of 1A / g, the HATTABQ and HATTAPT electrodes had first-cycle discharge specific capacities of up to 879.5mAh / g and 935.5mAh / g, respectively, but the first-cycle coulombic efficiencies were both less than 60%. At a current density of 10A / g, the HATTABQ electrode could reach a specific capacity of 260mAh / g, and when the current density returned to 1A / g again, the capacity could almost return to the initial stable specific capacity of 500mAh / g; at a current density of 5A / g, the HATTAPT electrode could reach a specific capacity of 330mAh / g, and when the current returned to 1A / g again, the specific capacity could almost return to the initial stable specific capacity of 490mAh / g.

Claims

1. A class of covalent organic polymer materials based on polyquinone imidazoles, characterized in that: The class of covalent organic polymer materials based on polyquinone imidazole includes HATTABQ and HATTAPT, and the structural formulas of HATTABQ and HATTAPT are shown in (I) and (II), respectively:

2. A class of covalent organic polymer materials based on polyquinone imidazole according to claim 1, characterized in that: The preparation method of HATTABQ comprises the following steps: dispersing compound 1 and compound 2 in ultrapure water, adding a catalyst, placing in a reaction kettle, reacting at 180° C. for 3 days, filtering, washing, and drying to obtain a black product HATTABQ; The preparation method of HATTAPT comprises the following steps: dispersing compound 1 and compound 3 in ultrapure water, adding a catalyst, placing in a reaction kettle, reacting at 180° C. for 3 days, filtering, washing, and drying to obtain a black product HATTAPT; The compound 1 is hexaazine naphthylic acid, the compound 2 is tetraaminobenzoquinone, and the compound 3 is 2,3,7,8- Tetraamino-1,4,6,9-tetraquinonephenoloxazine.

3. A class of covalent organic polymer materials based on polyquinone imidazole according to claim 2, characterized in that: The structural formulas of compound 1, compound 2 and compound 3 are shown as (III), (IV) and (V), respectively:

4. A class of covalent organic polymer materials based on polyquinone imidazole according to claim 2, characterized in that: The catalyst is 3M acetic acid solution.

5. A class of covalent organic polymer materials based on polyquinone imidazole according to claim 2, characterized in that: The molar ratios of compound 1 to compound 2 and compound 1 to compound 3 are both 1:1.

5.

6. A class of covalent organic polymer materials based on polyquinone imidazole according to claim 2, characterized in that: The drying condition is drying at 60° C. for 12 h.

7. Use of a class of covalent organic polymer materials based on polyquinone imidazole as claimed in claim 1 as negative electrode materials in lithium ion batteries.

8. The use according to claim 7, characterized in that: Here’s how: 1) Mixing the covalent organic polymer material based on polyquinone imidazole according to claim 1 with the conductive agent Super P and the binder CMC, adding the solvent H2O to grind into a uniform and particle-free slurry, and evenly scraping the slurry on the current collector with a tetrahedral mold; 2) Place the coated current collector in a 60°C vacuum drying oven and dry for 12 hours to remove the residual solvent, and then cut it into a circle with a diameter of 12 mm using a cutting machine to obtain an electrode sheet; 3) In an argon-protected glove box, the water and oxygen values ​​in the glove box are kept less than 0.1 ppm, and the electrode sheet, PP diaphragm, electrolyte, metal lithium sheet with a diameter of 16 mm, gasket, spring, and positive electrode shell obtained in step 2) are placed in the negative electrode shell in sequence using a 2032-type button cell standard; 4) Use a packaging machine to seal the battery to obtain a 2032-type button lithium-ion battery.

9. The use according to claim 8, characterized in that: In step 1), the mass ratio of a class of covalent organic polymer materials based on polyquinone imidazole: Super P: CMC is 6:3:1, and the current collector is copper foil.

10. The use according to claim 8, characterized in that: In step 3), the electrolyte is prepared by dissolving LiPF6 in a mixture of EC and DEC so that the concentration of LiPF6 is 1M and the volume ratio of EC and DEC is 1:1.

Citation Information

Patent Citations

  • Polyquinone polymer organic electrode material and preparation method and application thereof

    CN117843893A

  • Covalent organic framework material, preparation method thereof, electrode material, battery and application

    CN118373988A

  • Covalent organic framework material based on polybenzimidazoles as well as preparation method and application of covalent organic framework material

    CN118955901A

  • Conductive two-dimensional (2D) covalent organic frameworks (COFS) and method of making an electrode material

    US20230197361A1